Computer tomography of the facial skull - Tymofieiev О. О.; Ushko Н. О.; Maksymcha С. В.; Fesenko Є. І.; Ukharska О. А.; Blinova В. П.; Serga О. О.; Myroshnyk А. О. (Actual Dentistry, 2024)
Purpose: to present the Х-ray anatomy of the facial skull bones of healthy people in computed tomography images. Methods: computed tomography of facial skull bones. Results. The article presents the anatomy of the facial skull bones of healthy people in the images that were obtained during computed tomography. Conclusions. Knowledge of the X-ray anatomy of the facial skull bones allows to correctly interpret the results of computed tomography during diagnosis and differential diagnosis of maxillofacial pathology.